Agent-Based Models and Complexity Science in the Age of Geospatial Big Data Selected Papers from a workshop on Agent-Based Models and Complexity Science (GIScience 2016) (Advances in Geographic Information Science,, 2018)
This book contains a selection of papers presented during a special workshop on Complexity Science that took part of the 9th International Conference on GIScience 2016. Expert researchers in the areas of Agent-Based Modeling, Complexity Theory, Network Theory, Big Data, and emerging methods of Analysis and Visualization for new types of data explore novel complexity science approaches to dynamic geographic phenomena and their applications, addressing challenges and enriching research methodologies in geography in a Big Data Era.